2005
DOI: 10.1016/j.jacc.2005.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Diuretics and Bone Loss in Rats With Aldosteronism

Abstract: In aldosteronism, hypercalciuria and hypermagnesuria and accompanying decrease in plasma-ionized [Ca2+]o and [Mg2+]o lead to hyperparathyroidism that accounts for bone wasting. Furosemide exaggerates these losses, whereas its combination with spironolactone attenuates these responses to prevent bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 49 publications
0
43
0
2
Order By: Relevance
“…It has been well reported that aldosteronism affects bone metabolism; for instance, bone mineral and bone strength are lost in the presence of a high level of aldosterone. (60,61) Interestingly, two (NR3C2 and PIK3R1) of four pathway genes from the cluster have been demonstrated to be involved in bone metabolism. NR3C2 encodes mineralcortical receptor (MR) that is expressed in osteocytes, osteoblasts, and osteoclasts, (62) and aldosterone activation of MR promotes osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well reported that aldosteronism affects bone metabolism; for instance, bone mineral and bone strength are lost in the presence of a high level of aldosterone. (60,61) Interestingly, two (NR3C2 and PIK3R1) of four pathway genes from the cluster have been demonstrated to be involved in bone metabolism. NR3C2 encodes mineralcortical receptor (MR) that is expressed in osteocytes, osteoblasts, and osteoclasts, (62) and aldosterone activation of MR promotes osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…11 As is the case with ischemia/reperfusion injury or excess circulating catecholamines, intracellular Ca 2+ overloading is accompanied by the appearance of oxidative stress. This is expressed as (1) an activation of nicotinamide adenosine dinucleotide phosphate oxidase, a source of superoxide in vascular tissues; (2) an activation of a redox-sensitive transcription factor (NF)-κB, together with upregulated expression of the proinflammatory genes it governs; (3) reactive oxygen (e.g., superoxide, H2O2) and nitrogen (e.g., peroxynitrite) species in diverse tissues; and (4) 22 Secondary hyperparathyroidism with hypercalciuria has been observed in patients with advanced CHF awaiting cardiac transplantation and who had received chronic furosemide treatment. 23,24 These persons were also found to have a reduction in bone mineral density in keeping with osteopenia or, in more advanced cases, with osteoporosis.…”
Section: Chf: a Salt-avid Statementioning
confidence: 99%
“…(6) Furthermore, in an animal model with aldosteronism, due to aldosterone/salt treatment, loss of minerals and progressive reduction of cortical bone strength was observed, (7) subsequently rescued by spironolactone treatment. (8)(9)(10)(11) The aim of our study was to evaluate bone involvement in patients with primary aldosteronism (PA) consecutively recruited among the patients with adrenal incidentaloma (AI) referred to two tertiary care centers in Italy.…”
mentioning
confidence: 99%